2006
DOI: 10.1007/s00414-006-0077-y
|View full text |Cite
|
Sign up to set email alerts
|

Mother–child exclusion due to paternal uniparental disomy 6

Abstract: In a mother-child pair, false exclusions in markers on chromosome 6 have been observed. The genetic incompatibilities have been caused by paternal uniparental disomy. The consequences of such cases for investigations of parentage are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Although blood transfusion is not thought to affect DNA profiling [2], this medical information allowed to exclude chimerism associated with medical intervention (i.e., artificial chimerism) see, e.g., [3][4][5][6] as being the explanation of the observed pattern. Natural chimerisms resulting from the fusion of zygotes [7], from exchanges of blood between fetuses in utero, e.g., [8][9][10], or from double parental contribution, e.g., [11][12][13][14] as well as mosaicism are compatible with our data. Mosaics originate from somatic mutation and have generally only one STR locus altered [15,16], but cancer may considerably increase the mutability of genetic markers, e.g., [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 87%
“…Although blood transfusion is not thought to affect DNA profiling [2], this medical information allowed to exclude chimerism associated with medical intervention (i.e., artificial chimerism) see, e.g., [3][4][5][6] as being the explanation of the observed pattern. Natural chimerisms resulting from the fusion of zygotes [7], from exchanges of blood between fetuses in utero, e.g., [8][9][10], or from double parental contribution, e.g., [11][12][13][14] as well as mosaicism are compatible with our data. Mosaics originate from somatic mutation and have generally only one STR locus altered [15,16], but cancer may considerably increase the mutability of genetic markers, e.g., [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 87%
“…UPD may manifest as heterodisomy in which two different homologs are inherited from the same parent or isodisomy in which both homologs are identical 1,2 . UPD has recently attracted attention in parentage testing application because it has been found to be responsible for pseudo‐exclusion of paternity or maternity 3‐6 …”
mentioning
confidence: 99%
“…Surprisingly, the results revealed 2 more loci, D2S1772 and D2S441, on the same chromosome 2 that were not transmitted in a Mendelian style ( Table 1 ). Therefore, we concluded that this UPD might be the same as had been reported in earlier studies [Keller et al, 2010;Wegener et al, 2006;Ou X et al, 2013]. However, 4 of the STR loci were located on the short arm of chromosome 2 (TPOX at 2p25, D2S1338 at 2p35p36, D2S1772 at 2p13, D2S441 at 2p13).…”
Section: Function Prediction Of the Variantsmentioning
confidence: 63%